Regional Autonomy Policy Towards the Decentralization of Education in Indonesia: A Systematic Literature Review - Asyibli, Basri; Muiz, Rizqi Nurlaili; Sarmain, Sarmain; Muin, Abdul; Mu'izzuddin, Mochammad (REFORMASI, 2025)
This study aims to explore the influence of regional autonomy on the decentralization of education in Indonesia as well as the factors that affect the successful implementation of education policies at the regional level. The method used is a systematic literature review with the PRISMA approach, which involves identification, screening, and critical analysis of 28 relevant articles. The results of the study show that the decentralization of education provides opportunities to improve the quality and efficiency of education management. However, there are significant gaps in human resource capacity, infrastructure, and funding in various regions, which can hinder the achievement of equitable and quality education goals. The implications of this study emphasize the importance of support from the central government in terms of regulation and funding, as well as strong political will from local governments to advance the education sector. In addition, active community participation is also needed to create an education system that is responsive to local needs. With good collaboration between the central government, regions, and the community, it is hoped that the goal of educating the life of the nation can be achieved more effectively and evenly throughout Indonesia. This research provides important insights for policymakers in formulating better education strategies in the era of decentralization.Penelitian ini bertujuan untuk mengeksplorasi pengaruh otonomi daerah terhadap desentralisasi pendidikan di Indonesia serta faktor-faktor yang mempengaruhi keberhasilan implementasi kebijakan pendidikan di tingkat daerah. Metode yang digunakan adalah systematic literature review dengan pendekatan PRISMA, yang melibatkan identifikasi, skrining, dan analisis kritis terhadap 28 artikel yang relevan. Hasil penelitian menunjukkan bahwa desentralisasi pendidikan memberikan peluang untuk meningkatkan kualitas dan efisiensi pengelolaan pendidikan. Namun, terdapat kesenjangan signifikan dalam kapasitas sumber daya manusia, infrastruktur, dan pendanaan di berbagai daerah, yang dapat menghambat pencapaian tujuan pendidikan yang merata dan berkualitas. Implikasi dari penelitian ini menekankan pentingnya dukungan dari pemerintah pusat dalam hal regulasi dan pendanaan, serta political will yang kuat dari pemerintah daerah untuk memajukan sektor pendidikan. Selain itu, partisipasi aktif masyarakat juga diperlukan untuk menciptakan sistem pendidikan yang responsif terhadap kebutuhan lokal. Dengan kolaborasi yang baik antara pemerintah pusat, daerah, dan masyarakat, diharapkan tujuan untuk mencerdaskan kehidupan berbangsa dapat tercapai secara lebih efektif dan merata di seluruh Indonesia. Penelitian ini memberikan wawasan penting bagi pengambil kebijakan dalam merumuskan strategi pendidikan yang lebih baik di era desentralisasi.